They Are Girls, Not Mothers: The Violence of Forcing Motherhood on Young Girls in Latin America - Ximena Casas (Harvard FXB Center for Health and Human Rights, 2019)
Rape of girls under the age of 14 is common in Latin America, and forced pregnancy and motherhood among these girls is a major public health and human rights problem. Even though abortion in the case of rape is legal in a handful of the countries in the region, and is legal in most countries when the life or health of the pregnant woman is in danger, many girls under 14 are forced to continue pregnancies conceived due to rape and to become mothers long before they have the capacity to do so. The paper demonstrates how forced pregnancy and motherhood among girls aged 9-14 in the Latin America region who have been the victims of rape adversely affects all aspects of their health and lives, exacerbated by discrimination and the absence of legal abortion services. It then describes a multidimensional strategy, which includes legal, communications, and advocacy work developed by Planned Parenthood Global and partners in response to these realities. This unique strategy seeks to ensure that access to legal abortion is universally available and accessible to girls aged 9-14 on the grounds that continuing pregnancy poses a serious risk to their health and lives.